2016
DOI: 10.1002/jso.24320
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for recurrence in stage II/III colorectal cancer patients treated with curative surgery: The impact of postoperative tumor markers and an infiltrative growth pattern

Abstract: High-recurrence risk can be identified in stage II/III CRC patients by assessing perioperative serum tumor marker levels, lymphatic invasion, and infiltrative growth patterns. Intensive follow-up for patients with these risk factors may help detect recurrences promptly and improve survival. J. Surg. Oncol. 2016;114:368-374. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
(31 reference statements)
1
16
0
Order By: Relevance
“…However, the 5-year survival rate at stage IV is extremely poor (~ 18.8%) [ 6 ]. Moreover, CRCs recur after surgical resection in ~ 10% of patients with stage II disease and in ~ 20–40% with stage IIIa–IIIb disease; hence, recurrence remains an important concern [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the 5-year survival rate at stage IV is extremely poor (~ 18.8%) [ 6 ]. Moreover, CRCs recur after surgical resection in ~ 10% of patients with stage II disease and in ~ 20–40% with stage IIIa–IIIb disease; hence, recurrence remains an important concern [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, several studies have shown that the degree of parietal invasion was significantly associated with the risk of recurrence [27, 28]. A recent study by Chen et al involving 359 patients operated for rectal cancer showed that the T3 stage has a higher risk of recurrence compared to the T2 stage ( p = 0.012) [3].…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the third most common cancer worldwide, the fourth cause of cancer-related deaths [1], and is expected to increase by 60% by 2030 [2]. Even after radical resection, CRC recurrence is still a major concern [3,4]. The treatments for CRC include surgery, chemotherapy and/or radiotherapy, which are invasive treatments often associated with adverse side effects.…”
Section: Introductionmentioning
confidence: 99%